Analysis of Waste in the Production System with the Approach Lean Manufacturing Method - Utomo, Prastyo; Pudji, Endang (Journal La Multiapp, 2025)
Improving the production process needs to be done continuously and continuously in order to minimize all activities that consume time but do not contribute directly to the value of the products produced. PT Cipta Oggi is a manufacturing company that makes furniture products which has a major problem, namely the low value of Process Cycle Efficiency, which the company should have a PCE value of at least 50%. The use of lean manufacturing methods with the help of VSM is used to reduce waste in order to increase the PCE value. There are 22 non-added value activities with a time range of 427 minutes that can be cut. Where the production time was originally 1353 minutes to 926 minutes which had an impact on increasing Process Cycle Efficiency which was originally 46.8% to 68.4%. Based on Failure Mode and Effect Analysis (FMEA), it is known that the main root cause that has the highest RPN value is the Overprocessing waste with a score of 420 and the proposed improvements in order to reduce this waste are the need for safe storage management that can reduce the risk of damage to goods which requires additional processes, namely rework and additional human resources are needed in the inspection process in order to reduce the number of rework.